Dimensi Sosial dalam Hudud: Analisis Dimensi Sosial dalam Penerapan Hudud - Nur Fauzi Fatah; Nisa, Ulfatun Wahidatun (Journal of Islamic and Occidental Studies, 2023)
This article discusses the social aspects of ḥudūd within the context of Islamic society. Ḥudūd is a part of the Islamic legal system that functions to maintain social cohesion and uphold social values and norms. The descriptive-analytical method is employed with the aim of providing a clear and systematic overview of the phenomenon under investigation and conducting an in-depth analysis of the collected data. In this research, the researcher will identify and describe the key characteristics of the topic under study based on available literature, and subsequently conduct a comprehensive analysis of the qualitative data obtained from the research. The conclusion drawn is that the enforcement of ḥudūd has a positive influence in maintaining the stability of the Islamic society in several aspects. The punitive provisions within ḥudūd have the power to protect the social conditions of the Islamic community. This assessment is examined from the social aspects of ḥudūd, namely the restoration of social conditions following the occurrence of crimes, individual reform resulting in community rehabilitation, prevention of recurrence of crimes by other offenders, and fostering societal awareness of responsibility in safeguarding the public interest. Through this, ḥudūd provides social protection and ensures the realization of fundamental human rights within the society.